Small-scale dairying, stimulus for improving farm livelihoods - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The adoption of dairy farming can be the stimulus for a direct increase in farm earnings and a general improvement in farm productivity. Milk sales can provide a regular income throughout much of the year and with dual-purpose breeds the calf will...